Hyperactivity and attention disorders of childhood (Cambridge University Press, 2002)
Building on the success of the first edition and addressing the advances in the field since its publication, Seija Sandberg has brought together a distinguished, international team to review the area of attention-deficit and hyperactivity disorders (ADHD) in children and young adults. This new edition is thoroughly revised and updated, with new chapters dealing with the genetic background and the adult form of the disorder. Several of the topics dealt with in the first edition are being covered by new authors in the second